Pelestarian Kebudayaan Berbasis Kearifan Lokal di Era Globalisasi : Studi Kasus Kampung Adat Cirendeu - Juliansyah, Barkah; Nurhelmi, Anggita; Alfadhila, Sultan Aulia; Dikarsa, Asep Anggi; Aceng, Aceng; Supriadi, Supriadi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
In the fast-paced era of globalization, preserving local cultural resilience poses a unique challenge. Kampung Adat Cireundeu in West Java is an example of a community that has successfully maintained its local wisdom amidst the currents of modernization. This research examines the strategies for cultural resilience in Kampung Adat Cireundeu and the role of the government in supporting its sustainability. The study found that cultural preservation in Kampung Adat Cireundeu begins within the family environment, building self-awareness among young generations through traditional approaches such as "lengkah munggaran," house spatial arrangements, and strengthening family communication. Traditional-based education in the "bale atikan" serves as a medium for delving into local traditions. Support from the central government is manifested through legal protection, such as the recognition of cassava rice ("rasi") and the "Tutup Tahun Saka Sunda" traditional ceremony as Intangible Cultural Heritage (ICH) and the protection of Intellectual Property Rights (IPR). However, at the local government level, support remains suboptimal in terms of infrastructure development. This research emphasizes the importance of synergy between indigenous communities, the central government, and local governments in maintaining cultural resilience. Efforts that can be undertaken include the development of cultural infrastructure, capacity building for indigenous communities, and the integration of culture into local education. With a holistic approach, Kampung Adat Cireundeu can serve as a real-world example of success in preserving local wisdom in the midst of modernization.